KETEPATAN MODEL PREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN RETAIL DI INDONESIA - Kartikasari, Kartikasari; Hariyani, Diyah Santi (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2019)
Abstract This study aims to analyze the condition of Financial Distress in retail companies listed on the Indonesian Stock Exchange in 2015-2017 using the Ohlson Model, Fulmer Model, CA-Score Model and Zavgren Model. The data used in this study was secondary data derived from the financial statements of retail companies found on the Indonesian Stock Exchange. The data analysis technique used was inferential statistics and Kruskal-Wallis test. The results of this study indicated that Ohlson's model is best at predicting Financial Distress in retail companies in Indonesia with an accuracy rate of 83.33%, CA-Score Model with 30% accuracy rate, as well as the Fulmer Model and Zavgren Model with an accuracy rate of 0.00 %